Life ain't fair for a miner's son: Intergenerational outcomes for sons of US miners in the early twentieth century - Kelsey Carlston (Essays in Economic & Business History (EEBH), 2023)
In the early twentieth century, the mining industry was characterized by isolation, dangerous working conditions, employer power, and declining employment. However, miners also enjoyed high earnings, flexible schedules, and company housing. In this article, I explore intergenerational economic mobility for miners' sons. Using linked full-count US Census data to explore outcomes for miners' sons compared to other sons, I find that miners' sons usually do worse than manufacturing workers' sons but better than farmers' sons. Successful sons of miners grew up in urban neighborhoods that were mining-dependent, had access to education, and moved from their childhood counties. Sons of miners in the coal industry, which was shrinking, also did worse than sons of miners in the oil industry, which was expanding. This article sheds light on the effect that industry growth and geographic isolation has on intergenerational outcomes.
Keywords: J62; N32; N51; 330; ntergenerational Mobility; Mining; US Economic History; Labor History